2013
DOI: 10.1158/1535-7163.mct-12-1045
|View full text |Cite
|
Sign up to set email alerts
|

Potential Advantages of CUDC-101, a Multitargeted HDAC, EGFR, and HER2 Inhibitor, in Treating Drug Resistance and Preventing Cancer Cell Migration and Invasion

Abstract: CUDC-101 is a novel, small-molecule, anticancer agent targeting histone deacetylase (HDAC), EGF receptor (EGFR), and HER2. It is currently in phase I clinical development in patients with solid tumors. Previously, we reported that CUDC-101 has potent antiproliferative and proapoptotic activity in cultured tumor cells and in vivo xenograft models. We now show that cancer cells that have acquired resistance to single-target EGFR inhibitors through upregulation of AXL or loss of E-cadherin remain sensitive to CUD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 48 publications
2
48
0
Order By: Relevance
“…The impetus for the clinical development of CUDC-101 is based on the critical role that HDAC and RTK inhibitors play as cancer treatments, as well as the synergistic anticancer activity these inhibitors display when combined in preclinical setting. CUDC-101 displays potent antiproliferative and proapoptotic activity in in vitro and in vivo drug-resistant tumor models, including erlotinib-sensitive and resistant NSCLC cell lines as well as lapatinib-sensitive (HER2 positive) and resistant (HER2 negative) breast cancer models (18)(19)(20). Mechanistic studies have shown that CUDC-101 not only directly inhibits both EGFR and HER2 signaling but also indirectly attenuates signaling mediated by the HER3, MET, AXL, and AKT (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impetus for the clinical development of CUDC-101 is based on the critical role that HDAC and RTK inhibitors play as cancer treatments, as well as the synergistic anticancer activity these inhibitors display when combined in preclinical setting. CUDC-101 displays potent antiproliferative and proapoptotic activity in in vitro and in vivo drug-resistant tumor models, including erlotinib-sensitive and resistant NSCLC cell lines as well as lapatinib-sensitive (HER2 positive) and resistant (HER2 negative) breast cancer models (18)(19)(20). Mechanistic studies have shown that CUDC-101 not only directly inhibits both EGFR and HER2 signaling but also indirectly attenuates signaling mediated by the HER3, MET, AXL, and AKT (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…CUDC-101 displays potent antiproliferative and proapoptotic activity in in vitro and in vivo drug-resistant tumor models, including erlotinib-sensitive and resistant NSCLC cell lines as well as lapatinib-sensitive (HER2 positive) and resistant (HER2 negative) breast cancer models (18)(19)(20). Mechanistic studies have shown that CUDC-101 not only directly inhibits both EGFR and HER2 signaling but also indirectly attenuates signaling mediated by the HER3, MET, AXL, and AKT (18)(19)(20). CUDC-101 is an example of the strategy for simultaneous inhibition of multiple, biochemically distinct molecular targets that may address resistance mechanisms encountered by single-targeted therapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the in vitro and in vivo observations presented in this paper showing both additive and synergistic activity (36). Several reports have shown successful results in multiple myeloma (37)(38)(39). Here, we present evidence for the first time that AR42 and CHEK2i show promising preclinical activity using a human NHL xenograft model.…”
Section: Discussionmentioning
confidence: 52%
“…This involves the development of rational methods which combine the different structural features from ligands to produce multitargeted hybrids (Ai et al, 2012;Wang et al, 2013). The multitargeting approach also involves merging of different inhibitors that target a single specific target which could offer a successful means to treat certain diseases such as cancer, type 2 diabetes mellitus, and viral as well bacterial infections (Melisi et al, 2013).…”
Section: Class Iii: Multi-targeted Hybrids In Cancermentioning
confidence: 99%